If it isn't one thing . . . - Havill, Steven (Havill, Steven. Posadas County series., 2025)
"When a pickup truck pulling a horse trailer collides with a loaded semi, it seems like a straightforward accident. Undersheriff Estelle Reyes-Guzman presumes the most complicated part of the clean-up will be getting thirty tons of unsplit firewood off of Posadas County's state highway. But the plot thickens when the mangled vehicles are wrenched apart and the pickup's deceased driver is not who Estelle was expecting. Who is the dead man -- and where was he heading with his cargo, a prized stallion whose owner is frantic to get him back? And if it isn't one thing, it's another. Just as Estelle gets her teeth in the case, she's called to a domestic incident between a local volatile couple, which has led not just to death -- but to the injury of a fellow cop. Understaffed and overworked, Estelle finds herself plunged into two tricky investigations, which will take her across the border into Mexico to find the answers -- and the justice -- that she seeks." -- Dust jacket flap.